Development and Prevention of Aggressive Behavior: Intergenerational, Interdisciplinary, Experimental, and Historical Perspectives Since Aristotle - Tremblay, Richard E. (Journal of developmental and life-course criminology, 2022)
This paper is a summary of the research I did on the development, prevention and treatment of antisocial behavior over the past half century. It is also a reflection on the intellectual and cultural influences that guided my research, from the classic philosophers to my 21st century peers…including David Farrington.